High clarity polyurethane laminating adhesives based on poly (propylene glycol). Effect of hard segment on microphase morphology, haze and adhesion. (September 2022) - McCreath, S.; Boinard, P.; Boinard, E.; Gritter, P.; Liggat, J.J.
Abstract: Within this publication, the performance of high clarity polyurethane adhesives based on a poly(propylene glycol) soft-phase within a polycarbonate or ethanolamine surface-treated polycarbonate laminate, is described. A series of polyurethanes were prepared, with poly(propylene glycol) used as soft-phase due to the high clarity of this polyol and absence of carbonyl functionality, which allows for hard-phase architecture to be resolved with greater resolution. In total, eight adhesives were synthesised, each contained a different chain-extender formulation to gauge what influence hard-phase architecture had on laminate haze and peel strength. This was investigated using either 4, 4-methylene diphenyl diisocyanate or isophorone diisocyanate as hard-phase with trimethylolpropane as the only chain-extender or by including one of the following sterically hindered diols: 2, 2-diethyl-1, 3-propane diol, 1, 3-butane diol or 1, 2-proane diol. DSC analysis showed that microphase morphology was strongly influenced by the diisocyanate present, as shown by the degree of phase mixing being greater in methylene diphenyl diisocyanate based formulations when compared with isophorone diisocyanate based. ATR complements this observed difference in microphase morphology, with isophorone diisocyanate based formulations having a greater composition of hydrogen-bonded urethane and urea functionality present within the hard-phase which displays a more phase separated composition. Interestingly, differences in microphase mixing did not have a consistent influence on the peel strength obtained, with only 31% of laminate combinations tested recording a peel strength of <3 N mm −1 after 18 months. Diol chain-extended formulations based on methylene diphenyl diisocyanate accounted for 25% of these lower values and was a consequence of their poorer process-ability during lamination. This resulted in higher haze values being encountered for both polycarbonate and ethanolamine surface-treated polycarbonate laminates which contained methylene diphenyl diisocyanate based formulations when compared to isophorone diisocyanate based formulations, where all values were <1.5%.